Sweet corn (Zea mays L.) growth and yield are influenced by establishment methods - Ceccoli, Gabriel (2014)
Six experiments were performed in the term of three years in order to explore and compare the effects of transplanting and direct sowing (DS) on sweet corn (Zea mays L.) growth, earliness and yield. Different genotypes, tray cell sizes (volume) and seedling ages were assayed. In all experiments, direct sowing was performed with a final separation of 0.25 m between plants in each row. Growth parameters (height, leaf area and ear size) were reduced with the increase of age and/or decrease of the tray cell size, mainly in cultivars with early flowering i.e., low cumulative corn heat unit (CHU) requirements. Earlier harvests were obtained in transplanting compared to direct sowing, although with lower yields. When the thermal time accumulated by plants in the trays was higher than 100 CHU, the yield decreased by 3.91% (R2 = 0.79) for each unit of CHU. The results indicate that the transplanted sweet corn yield was generally lower than of direct seeded plants, and differences grew bigger as the tray cell volume was smaller and the seedlings age increased.